Girth Class of Sal Trees Prone to the Attack of Heartwood Borer, Hoplocerambyx spinicornis Newman (Coleoptera: Cerambycidae) - Roychoudhury, N.; Sambath, S.; Joshi, K. C. (Indian Forester, 2004)
An experiment was laid out in Sal forest at Jagatpur under Karangia Range of Mandla division during the recent epidemic of Sal heartwood borer, Hoplocerambyx spinicornis Newman, in Madhya Pradesh, with a view to find out the girth class preference of the insect in Sal trees and subsequent mortality. Results based on four years observations revealed that total per cent mortality of Sal trees due to borer attack was recorded to be 5.17% in experimental plot. The results reflect the post effect of Sal borer epidemics. The borer attack was noticed from the girth class more than 61-90cm (4.24%),91-120 cm (5.08%) and finally peak in 121-150 cm (6.78%) and then declined in girth class above 151 cm (3.12%). Further, the frequency distribution of girth class of Sal trees and tree mortality due to borer attack exhibited maximum mortality in 102-116 and 117-131cm ranges. These findings clearly advocate the girth class preference by borer beetles in Sal forests.